The Talent Equation: Managing Millennials and Generation Z in the Modern Workplace - Rafikha Anggraini; Rozie Meidy; Kris Suspon Rama; Solina Balqis; Pika Meri Yanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This Study aims to explore human resource management (HRM) approaches in responding to the challenges and opportunities arising from the presence of Millennials and Generation Z employees in today’s workplace. Using a descriptive qualitive method, data were collected through in-depth interviews involving employees from both generation as well as HR practitioners across various industrial sectors. The findings reveal that Millennials and Gen Z possess distinctive characteristics that influence their preferences regarding work systems, leadership styles, and career development paths. Consequently, companies are required to adopt flexible, technology-based managerial strategies that can be tailored to individual needs. Approaches such as flexible working arragements, digital training, and transparent communication have proven effetive in enhancing employee engagement and loyalty. This study highlights the importance of creating a balance between organizational goals and the values of the younger generations to foster an innovative and sustainable work environment.